Robin in the middle - Pascal, Francine (Bantam Books New York, 1993)
Identical twins Elizabeth and Jessica Wakefield can't wait for their cousin Robin to come for a visit. But when Robin arrives, both twins like her so much that they don't want to share her--even with each other. Soon they're fighting for Robin's attention. Can the three girls ever learn to play together?.